Mild and Efficient Reagents for Oxidation of Alcohols: [MeOCH2(Ph)3P]+[CrO3X]ֿ, (X=F, Cl) - Amir Lashgari; Shahriar Ghamami (The Journal of Pure and Applied Chemistry Research, 2015)
Two fast, mild, and reasonable oxidizing agents, Methoxymethyltriphenylphosphonium Halochromates (VI), [MeOCH2(Ph)3P]+ [CrO3X]ֿ (MMTriPPXC) are synthesized. The preparations of Methoxymethyltriphenylphosphonium Halochromates are new and efficient reagents for the oxidation of primary and secondary alcohols to their corresponding carbonyl compounds in dichloromethane at ambient temperature. These are obtained with relatively short reaction times.  The oxidants/substrates ratios of 1:1 are employed.